Analisa Dan Perancangan Sistem Informasi Penggajian Buruh Pada Cv Lampung Robusta Coffee Berbasis Android - adi prasetia nanda; m ikhsan; ridwan yusuf (Jurnal Multimedia dan Android (JMA), 2020)
AbstractCV Lampung Robusta Coffee is a company that sells agricultural produce in the form of coffee, chocolate and others. Since its inception until now the system used in the processing of payroll data, especially labor payroll is still using a manual system for recording and calculating payroll. In the case of labor payroll calculations and bookkeeping, there are often errors in recording and calculations that cause labor payroll data to be inaccurate, so the administration must recalculate and replace the wrong records. For that we need a system that is able to accommodate data into a database and a system that is able to calculate assessments based on the type of work accurately. Based on the background of the problems above, the writer takes the title